How does technological innovation impact the service time and the attraction of new customers in the financial sector? Evidence from an emerging economy - Lorena Reyes-Rubiano; Ingrid Y. Amaya; David Medina Mayorga; Andrés Mu\~noz-Villamizar; Elyn Solano-Charris (Operations Management Research, 2024)
Abstract Due to safety perceptions, Colombian banking clients prefer to visit bank branch offices instead of other channels. Thus, there are long waiting for lines at branch offices. Considering the need for more tools for strengthening and streamlining client service, the number of financial clients tends to diminish. In this context, this paper aims to measure the impact of technological innovation on the clients' waiting time and the attraction of new customers. We propose a simulation-based methodology to analyze customer behaviors and forecast the diffusion effect on mobile app adoption. Furthermore, our study provides managerial insights and future research lines.
Keywords: 330; Banking clients; Service level; Mobile App; Agent-based simulation; Bass diffusion model